Chimeric autoantibody receptor T cells specifically eliminate Graves’ Disease autoreactive B cells - Abigail Cheever; Hunter G. Lindsay; Chloe C. Kang; Mackenzie Hansen; Kimball Demars; Kim L. O’Neill; K. Scott Weber (Frontiers in Immunology)
IntroductionChimeric antigen receptor (CAR) T cells have recently become an important treatment for hematological cancers by efficiently eliminating B cells. B cell depleting CAR T cells are also in clinical trials for their use in treating severe autoimmune diseases and have shown promise in patients who have exhausted other treatment options; however, they do result in immunosuppression due to B cell depletion. Specifically eliminating the disease-causing B cells while leaving the healthy B cells untouched could address this limitation.MethodsA chimeric autoantibody receptor (CAAR) has an autoantigen as the binding domain of the CAR T cell and could allow for specific targeting of autoreactive B cell populations. In Graves’ Disease (GD), pathogenesis is centered around autoreactive B cells which are specific for thyroid stimulating hormone receptor (TSHR). By engineering epitopes of TSHR as the binding domain, our CAAR was able to bind to anti-TSHR antibodies and B cell receptors.ResultsThese TSHR CAAR T cells specifically eliminated anti-TSHR B cells, without exhibiting cytotoxicity against healthy B cells. We hypothesized that soluble autoantibodies and thyroid stimulating hormone (TSH) could bind to the CAAR, potentially causing overactivation or inhibition. When evaluated, we found that one construct was significantly impacted by soluble autoantibodies, while the other construct was uninhibited. Soluble TSH did not significantly affect either construct. The TSHR CAAR T cells were also effective at eliminating anti-TSHR B cells in the presence of plasma from various GD patients.DiscussionThus, TSHR CAAR T cells show promise in eliminating the disease-causing autoreactive B cells in GD without eliminating healthy cells. This treatment mechanism also has the potential to be used in other B cell-mediated autoimmune diseases.